Nomenclatural updates on names linked to the genus Axonopus for the Brazilian flora (Poaceae, Panicoideae, Paspaleae) - Delfini Feliciano, Carolina (2023)
A nomenclatural update for 20 names related to the genus Axonopus for the Brazilian flora is here presented. Axonopus comprises around 90, mostly New World, species characterized by having solitary spikelets in an inverted position. In order to stabilize the nomenclature and, based on thorough study of original collections and pertinent literature, we designated lectotypes for nine names, of which three are second-step lectotypes. We also corrected to lectotypes erroneous applications, in previous contributions, of the term “holotype” (for four names), clarified three cases in which lectotypification is not required, as well as discussed four situations of uncertainty.